Injury to the Meniscofemoral Portion of the Deep MCL Is Associated with Medial Femoral Condyle Bone Marrow Edema in ACL Ruptures. Issue 4 (11th October 2021) - Moran, Jay; Katz, Lee D.; Schneble, Christopher A.; Li, Don; Kahan, Joseph B.; Wang, Annie; Porrino, Jack; Jokl, Peter; Hewett, Timothy E.; Medvecky, Michael J.
Abstract : Background: The primary goal of the present study was to investigate injury to the deep medial collateral ligament (MCL), specifically the meniscofemoral ligament (MFL) portion, and its association with medial femoral condyle (MFC) bone marrow edema in acute anterior cruciate ligament (ACL) ruptures. The secondary goal was to examine the association between MFL injury and medial meniscal tears (MMTs) in these same patients. Methods: Preoperative magnetic resonance imaging (MRI) scans of 55 patients who underwent ACL reconstruction surgery were retrospectively reviewed by 2 board-certified musculoskeletal radiologists. MRI scans were examined for MFC edema at the insertion site of the MFL. This site on the MFC was referred to as the central-femoral-medial-medial (C-FMM) zone based on the coronal and sagittal locations on MRI. The presence or absence of bone marrow edema within this zone was noted. The prevalence, grade, and location of superficial MCL and MFL injuries were also recorded on MRI. The correlations between MFL injuries and the presence of MFC bone marrow edema were examined. Lastly, the presence and location of MMTs were also recorded on MRI and were confirmed on arthroscopy, according to the operative notes. Results: On MRI, 40 (73%) of the 55 patients had MFL injuries. MFL injuries were significantly more common than superficial MCL injuries (p = 0.0001). Of the 27 patients with C-FMM bruising, 93% (25 patients) had MFL tears (p < 0.00001). In addition, of the 40 patients with an MFL injury, 63% (25 patients) had C-FMM bruising (p = 0.0251). Chi-square testing showed that MMTs and MFL injuries were significantly associated, with 12 (100%) of 12 patients with MMTs also having a concomitant MFL injury (p = 0.0164). Conclusions: The prevalence of MFL injury in ACL ruptures is high and MFC bone marrow edema at the MFL insertion site should raise suspicion of injury. MFL injuries can present with clinically normal medial ligamentous laxity in ACL ruptures. Additionally, MFL injuries were significantly associated with posterior horn MMTs, which have been shown in the literature to be a potential risk factor for ACL graft failure. Clinical Relevance: As deep MCL injuries are difficult to detect on physical examination, our findings suggest that the reported MFC edema in ACL ruptures can act as an indirect sign of MFL injury and may aid in the clinical detection. Additionally, due to the anatomical connection of the deep MCL and the meniscocapsular junction of the posterior horn of the medial meniscus, if an MFL injury is suspected through indirect MFC edema at the insertion site, the posterior horn of the medial meniscus should also be assessed for injury, as there is an association between the 2 injuries in ACL ruptures.